Latent profiles of youth social support: a study on variations and their impact on self-esteem - Yu, Jingxian; Guo, Yuqin; Liang, Yongqi; Peng, Huan; Li, Na; Gu, Weisheng; Liu, Hanjiao (Frontiers in Psychology, 2025)
IntroductionThe current significant suicide rate reflects the urgency of addressing mental health problems among young people. At the same time, social support and self-esteem are key factors affecting young people’s mental health and suicide risk. Therefore, this study aims to explore the variations in perceived social support among youth using a latent profile analysis approach and examine its association with self-esteem.MethodsQuestionnaires were distributed using a simple random sampling technique in Shenzhen and Shaoguan, Guangdong Province. Data were collected using the multidimensional perceived social support scale and the self-esteem scale, and descriptive analysis and potential profile analysis were performed using SPSS and R.ResultsThis study identified three potential categories of perceived social support: “High Social Support” (55.7%), “High Friend Support and Moderate Social Support” (34.35%), and “Low Social Support” (9.95%), and young people who work in the service industry, are widowed, have two or more children, and have high academic achievement are likely to have worse perceived social support. Self-esteem was positively related to the categories of perceived social support, and the group with low social support had the lowest self-esteem.DiscussionMost young people have a high level of perceived social support, but a low perceived social support group needs more attention and help. It is suggested that both social support and self-esteem should be paid attention to maintain young people’s mental health.